Absorbable copolymers with improved thermal stability

JP2025010531A5Active Publication Date: 2025-03-19POLY MED INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024148586
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2014-12-19
Filing Date
2024-08-30
Publication Date
2025-03-19
Estimated Expiration
2035-12-18

AI Technical Summary

Technical Problem

Existing absorbent polymers lack thermal stability, molecular weight consistency, and intrinsic viscosity retention after melt extrusion, and the fibers made from these polymers do not exhibit sufficient strength and toughness.

Method used

The development of absorbable aliphatic polyester copolymers with a multiaxial core and flexible connecting segments, featuring crystallizable polymer chains and end-grafts, synthesized using a two-step process with controlled monomer-to-catalyst ratios and ring-opening polymerization in the melt or solid state.

Benefits of technology

The new copolymers demonstrate improved thermal stability, molecular weight consistency, and higher intrinsic viscosity retention, resulting in fibers with enhanced strength and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide absorbable block copolymers with improved characteristics including thermal stability, molecular weight consistency, and inherent viscosity retention following melt extrusion, and uses thereof.SOLUTION: A polymer includes a polyaxial core, with at least three axes, and a pre-polymer. The at least three axes comprise polymeric chains. There is also at least one flexible linking segment. Further, at least one polymeric end graft is attached to each of the at least three axes, and comprises repeat units derived from at least one cyclic monomer capable of crystallization.SELECTED DRAWING: Figure 6A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to absorbent copolymers having improved properties including thermal stability, molecular weight consistency, and intrinsic viscosity retention after melt extrusion, as well as methods for making the improved absorbent copolymers. The present invention further relates to absorbent fibrous constructs that can be used for controlled drug delivery. [Background technology]

[0002] Previous work in the polymer field, such as Shalaby's U.S. Patent No. 6,462,169, has disclosed multiaxial block copolyesters containing high glycolide end grafts. However, the polymers from this disclosure lack various properties compared to the present disclosure, such as thermal stability, molecular weight consistency, and intrinsic viscosity retention after melt extrusion. Furthermore, fibers produced from the '169 disclosure lack the strength and toughness exhibited by fibers produced from the polymers of the present disclosure. Furthermore, the polymers disclosed in '169 are limited to multiaxial block structures synthesized in the solid state at 180°C. The polymers of the '169 disclosure are synthesized in two steps, which require first synthesizing a prepolymer and then end grafting to obtain crystallizable end segments. The end segments are synthesized by reacting the prepolymer with monomers at 180°C until the reaction contents are solid, followed by continuing the reaction in the solid state at the same temperature for more than two hours.

[0003] Furthermore, Shalaby, U.S. Patent No. 6,498,229, discloses high glycolide block copolymers synthesized in the solid state. The polymers disclosed in the '229 patent, by way of example only and not by way of limitation, are synthesized with a higher amount of catalyst than those used to synthesize the high glycolide polymers of the present disclosure. Specifically, the '229 polymers are synthesized with a monomer to catalyst (M / C) ratio of 60,000. Not only are the polymers obtained from the '229 patent disclosure formed from solid state synthesis using more catalyst, they also lack the thermal stability, molecular weight consistency, and inherent viscosity retention after melt extrusion characteristics of the polymers produced according to the present disclosure. Furthermore, the '229 reference is limited to polymer compositions synthesized in a single-step reaction. The polymers also contain less than 80 mol % (and more than 20 mol %) of glycolide-derived repeat units. Furthermore, the two-step synthesis method in '229 can have "rather poor reproducibility." However, unexpectedly, and in contrast to the '229 disclosure, the polymers of the present disclosure show more than adequate reproducibility despite being synthesized by a two-step method. Additionally, Shalaby, U.S. Patent No. 6,342,065, discloses high lactide block copolymers synthesized in the solid state by a two-step process. However, the polymers resulting from the '065 disclosure lack the thermal stability, molecular weight consistency, inherent viscosity retention after melt extrusion, and improved fiber strength of the polymers of the present disclosure. Additionally, Zhao, US Patent No. 7,265,186, discloses multiaxial constructs having hydrophilic cores as star block copolymers, which cores are not hydrolytically degradable.

[0004] On the other hand, US Patent No. 8,262,723 discloses implantable medical devices made from branched / multiaxial polymers. Wang describes branched / multiaxial constructs, but the multiaxial block is always present with a second, different polymer having the same chemical structure as the end block of the multiaxial block. The present disclosure provides a discrete phase that does not constitute a blend of the multiaxial end block with a second polymer and a second phase comprising a prepolymer. The novel compositions disclosed herein form distinct discrete phases formed from blocks of end grafts and / or blocks of prepolymer. In the present disclosure, when the multiaxial may be present in combination with a second polymer having the same or similar composition as the end block of the multiaxial, the chain length and degree of polymerization of the second polymer are twice that of the end block of the multiaxial. Furthermore, Wang does not disclose flexible linking segments as disclosed herein. Jakubowski, U.S. Patent No. 8,569,421, describes multiaxial polymers having multiple axes. However, these compositions are not symmetrical and are purposely designed to have unsaturated bonds distributed at specific positions along the polymer arms, making the polymers more oxidatively stable. Jakubowski constructs are not intended to be biodegradable / absorbable. Furthermore, they are not specifically directed to implantable compositions. Himes, US Patent No. 5,639,831, is directed to multiaxial block copolymers for different applications than the present disclosure, and furthermore does not require the same chemical functionality and biocompatibility as the polymers of the present disclosure. It is therefore an object of the present invention to provide absorbent copolymers having thermal stability, improved molecular weight consistency, higher intrinsic viscosity retention after melt extrusion, and fibers made from the copolymers exhibiting increased strength. Summary of the Invention

[0005] The above object is achieved according to the present invention in a first embodiment by providing an absorbent aliphatic polyester copolymer, the copolymer comprising a multiaxial core having at least three axes and a prepolymer, the at least three axes comprising polymer chains, and at least one flexible bond segment, further comprising at least one polymer end graft attached to each of the at least three axes, the end graft comprising repeat units derived from at least one cyclic monomer capable of crystallization. In a further embodiment, the multiaxial core comprises a crystallizable polymer chain segment. Alternatively, the multiaxial core comprises an amorphous chain segment. In another embodiment, the flexible bond segment and the crystallizable cyclic monomer share a common monomer. In another embodiment, the flexible bond segment is composed of the same prepolymer as the multiaxial core and the same crystallizable cyclic monomer as at least one polymer end graft.

[0006] Furthermore, the prepolymer may be a homopolymer, copolymer or terpolymer formed from the group consisting of L,L-lactide, D,L-lactide, glycolide, substituted glycolide, paradioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, delta-valerolactone, or a combination thereof. Furthermore, the prepolymer may be derived from ε-caprolactone, trimethylene carbonate, or a combination of the two. Furthermore, the prepolymer may be derived from glycolide, trimethylene carbonate, or a combination of the two. In a further embodiment, the copolymer comprises at least four different blocks including a central crystallizable core having at least three axes, which includes crystallizable end blocks grafted on at least three axes. Furthermore, the at least one crystallizable cyclic monomer may be selected from the group consisting of L,L-lactide, D,L-lactide, glycolide, substituted glycolide, paradioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, delta-valerolactone, or a combination thereof. In another embodiment, the flexible bond segment may be derived from trimethylene carbonate, ε-caprolactone, or a combination of the two. Furthermore, the polyester copolymer may comprise an absorbent barrier, web, mesh, or fabric. Furthermore, the copolymer may be formed into a warp knit mesh. Furthermore, the copolymer may comprise an absorbent polymer surface coating for controlled drug delivery.

[0007] In another embodiment, a method for producing an absorbent aliphatic polyester copolymer is provided. The method includes the steps of charging a monomer, an initiator, and a catalyst into a reactor, with a monomer to catalyst ratio of at least 25,000. The initiator may have at least one hydroxyl group capable of initiating ring-opening polymerization. The monomer may include at least one cyclic monomer. The reactor is heated to at least 100°C. The monomer may be stirred to form a homogeneous mixture prepolymer, the prepolymer having a mass of greater than 10 kDa. A copolymer may then be formed having a plurality of amorphous prepolymer stalks and crystalline end grafts extending from each stalk.

[0008] In further embodiments, the catalyst may be stannous octoate. Other catalysts include Sn(Oct)2, Sn(OTf)2, dibutyltin(II)-2-ethylhexanoate (Bu2Sn(Oct)2), 4-(dimethylamino)pyridine (DMAP). Furthermore, the initiator may be selected from the group consisting of hydroxyl-bearing small molecules, oligomers, polymers, inorganic salts, organic salts, or combinations of the above. Furthermore, the initiator may be selected from the group consisting of 1-decanol, 1,3-propanediol, trimethylolpropane, triethanolamine, 1,3,4-trihydroxy-2-butanone, glycerol, or combinations of the above. In further embodiments, the monomer may be a copolymer or terpolymer derived from lactide, trimethylene carbonate, and / or ε-caprolactone. In yet a further embodiment, the monomer may be a copolymer or terpolymer derived from glycolide, trimethylene carbonate, and / or ε-caprolactone. In another embodiment, the monomer may be a substituted glycolide. In a further embodiment, a second charge of catalyst may be added to the reactor. In a further embodiment, two independent temperature settings may be established during the reaction. Structures designed to carry out the invention will now be described together with other features of the invention. The invention will be more readily understood from reading the following description and from the accompanying drawings which form a part thereof, in which an example of the invention is shown. [Brief description of the drawings]

[0009] [Figure 1] 1 is a graph showing the thermogravimetric analysis (TGA) of a polymer of the present invention. [Diagram 2] FIG. 1 illustrates one embodiment of the present disclosure in the form of a warp-knit 3-bar construction. [Diagram 3] FIG. 1 illustrates one embodiment of the present disclosure in the form of a tricot warp knit two-bar construction. [Figure 4] FIG. 1 illustrates one embodiment of the present disclosure in the form of a warp knitted two-bar "sharkskin" construction. [Diagram 5] FIG. 1 illustrates another embodiment of the present disclosure in the form of a half tricot pattern. [Figure 6A] FIG. 1 shows a fully extended chain depiction of a semi-crystalline multiaxial block copolymer. [Figure 6B] FIG. 1 shows an amorphous multiaxial core with polymeric amorphous arms having crystallizable end grafts. [Figure 7A] FIG. 1 shows a multiaxial block copolymer without flexible linkers connecting the prepolymers to the end grafts. [Figure 7B] FIG. 1 shows polymer constructs with flexible linker prepolymers and end grafts. [Figure 8] 1 is a formula showing the remaining prepolymer after mixing and reacting a second charge using prepolymer at a high catalyst concentration. [Figure 9] Data showing incomplete mixing / inhomogeneity from GPC analysis. [Figure 10] 9 shows data illustrating the analysis of the polymer of FIG. 8. [Figure 11] FIG. 1 illustrates a polymer of the present disclosure. [Figure 12] FIG. 2 shows another embodiment of a multiaxial block copolymer comprising multiple segments. [Figure 13] FIG. 1 shows an axially oriented four-arm multiaxial copolymer. [Figure 14] FIG. 14 is an excerpt from FIG. 13 showing exemplary arm polymer chain folding leading to chain-folded crystals. [Figure 15] FIG. 1 shows an asymmetric multiaxial copolymer. [Figure 16] FIG. 1 shows a hyperbranched microstructure polymer.

[0010] It will be understood by those skilled in the art that one or more aspects of the invention can fulfill certain objectives, while one or more other aspects can fulfill certain other objectives. Each objective may not be equally applicable in all respects to all aspects of the invention. Thus, the above objects can be viewed as alternatives with respect to any aspect of the invention. These and other objects and features of the invention will become more fully apparent from the following detailed description, taken in conjunction with the accompanying drawings and examples. However, it should be understood that both the foregoing summary of the invention and the following detailed description are preferred embodiments and are not intended to limit the invention or other alternative embodiments of the invention. In particular, while the invention has been described herein with reference to many specific embodiments, it should be understood that the descriptions are illustrative of the invention and are not to be construed as limiting the invention. Various modifications and applications will be possible to those skilled in the art without departing from the spirit and scope of the invention, as set forth by the appended claims. Similarly, other objects, features, advantages and benefits of the invention will be apparent from this summary and certain embodiments described below, and will be readily apparent to those skilled in the art. Such objects, features, advantages and benefits will become apparent from the above, taken alone or in light of the references incorporated herein, together with the accompanying examples, data, drawings and all reasonable inferences to be derived therefrom. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will now be described in more detail with reference to the drawings. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the subject matter disclosed herein belongs. Although any methods, devices, and materials similar or equivalent to those described herein can also be used in the practice or testing of the subject matter disclosed herein, representative methods, devices, and materials are described herein. The present disclosure relates to absorbent aliphatic polyesters with improved properties including thermal stability, molecular weight consistency, and inherent viscosity retention after melt extrusion. Furthermore, fibers made from the polymers will have increased strength. In one embodiment, the aliphatic polyesters of the present disclosure may include linear crystalline block copolymers such as diblock, triblock, and pentablock copolymers, synthesized from prepolymers that can be either amorphous or crystalline. In another embodiment, the aliphatic polyesters of the present disclosure may include linear crystalline random or segmented copolymers, all synthesized in a single reaction step without prepolymers. In a further embodiment, the aliphatic polyesters of the present disclosure may include multiaxial crystalline block copolymers (having at least three axes), synthesized from triaxial prepolymers that can be either amorphous or semi-crystalline. In yet a further embodiment, the aliphatic polyesters of the present disclosure may include multiaxial, crystalline segmented, or random copolymers, all synthesized in a single reaction step without prepolymers. In still further embodiments, the polyester may be synthesized from cyclic monomers such as glycolide, lactide, para-dioxanone, trimethylene carbonate, ε-caprolactone, morpholinedione, and mixtures thereof. In still further embodiments, the polyester may be synthesized from an initiator compound containing from one to at least three hydroxyl groups capable of initiating ring-opening polymerization. In further embodiments, the polyester may be a high glycolide copolymer containing a small amount of at least one additional monomer. By "high," it is meant that the polymer may contain at least 50 mole % glycolide derived repeat units, at least 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or more glycolide derived repeat units. Ranges of glycolide molar content are also contemplated by the present disclosure, including ranges of 50-60%, 60-70%, 70-80%, 80-90%, and 90-100%.

[0012] In a preferred embodiment, the high glycolide copolymer may be a highly crystalline multiaxial block copolymer, the block copolymer being synthesized in two steps. The copolymer may contain a triaxial amorphous prepolymer and a highly glycolide crystalline end graft at the end of each of the three prepolymer arms. In yet a further preferred embodiment, the high glycolide copolymer may be a highly crystalline multiaxial block copolymer, the block copolymer containing a triaxial crystalline prepolymer and a highly glycolide crystalline end graft at the end of each of the three prepolymer arms. In yet a further preferred embodiment, the high glycolide copolymer may be a highly crystalline multiaxial segmented copolymer, the segmented copolymer being synthesized in a single reaction step without the synthesis of a prepolymer. Furthermore, since the segmented copolymer lacks a prepolymer, there are no distinct "blocks" within the polymer structure. In a further embodiment, the polyester may be a high lactide copolymer containing a small amount of at least one additional monomer. By "high," it is meant that the polymer may contain at least 50 mole percent lactide-derived repeat units, at least 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or more lactide-derived repeat units. Ranges of lactide molar content are also contemplated by the present disclosure, including ranges of 50-60%, 60-70%, 70-80%, 80-90%, and 90-100%.

[0013] In an even more preferred embodiment, the high glycolide copolymer may be a highly crystalline multiaxial block copolymer synthesized in a two-step process that requires the synthesis of a crystalline prepolymer from caprolactone and trimethylene carbonate, followed by end-grafting of the prepolymer with glycolide and caprolactone to obtain the final block copolymer. This composition contains four distinct blocks: a central crystalline block with three axes and three crystalline end-graft blocks emanating from each of the three chain ends of the central block. The absorbent copolymers of the present disclosure may be formed by methods that include ring-opening polymerization carried out in the solid state and / or in the melt. In a preferred method, the absorbent copolymers of the present disclosure may be synthesized in the melt, which requires that the reaction be carried out at a temperature above the melting temperature of the copolymer being synthesized. In another preferred method, the absorbent copolymers of the present disclosure may be synthesized in the solid state, or the reaction may be terminated when the reaction product becomes too thick to stir and / or begins to crystallize. Ring-opening polymerization ("ROP") carried out in the melt and in large reactors such as 8 CV reactors is superior to solid state synthesis for forming the copolymers of the present application, especially when batch sizes greater than 1 kilogram are desired.

[0014] In one embodiment, the reaction may be carried out by charging the monomers and initiator into an 8 CV reactor, followed by heating the reactor to 100° C. under nitrogen (g), then stirring the molten monomers and initiator to produce a homogenous mixture, and finally adding the catalyst and raising the reaction temperature above the melting temperature of the polymer being synthesized. The reactor contents are stirred “in the melt” and the reaction is run until maximum conversion of the monomers to polymer. The molten polymer is then removed from the bottom of the reactor when maximum conversion is reached. This synthesis technique is commonly referred to as the “melt” technique. On the other hand, solid state synthesis limits the amount of polymer that can be synthesized in any one batch. However, by utilizing larger reactors suitable for ROP in the molten state, polymer may be produced in 7.5 kilogram batches in an 8 CV reactor, or on a larger scale of much more than 7.5 kilograms for larger reactors. This is in comparison to solid state reactions carried out in smaller reaction vessels such as 1 liter kettles. Initiators for the reaction may include compounds having one to three hydroxyl groups capable of initiating ring-opening polymerization. Examples include, but are not limited to, 1-decanol, 1,3-propanediol, trimethylolpropane, triethanolamine, 1,3,4-trihydroxy-2-butanone, and glycerol, or combinations of the above. Meanwhile, the preferred catalyst for these ROP reactions is stannous octoate. However, other catalysts known to those skilled in the art may be used. The polymers resulting from the methods disclosed herein may be copolymers that are linear or multiaxial in structure, and they may be either segmented or block copolymers. Thus, prepolymers may or may not be used in the synthesis of the copolymers of the present disclosure.

[0015] Figure 1 is a graph showing the thermogravimetric analysis (TGA) of the polymers of the present invention. Semi-crystalline linear block copolymers were tested. By way of example only and not intended to be limiting, triblock copolymers with a midblock derived from a prepolymer and semi-crystalline end grafts were tested. In one embodiment, the prepolymer included TMC and caprolactone, and the end grafts included l-lactide and TMC. As shown in FIG. 1, in the present disclosure, increasing thermal stability is obtained by decreasing the catalyst content. The amount of catalyst is described as the ratio of moles of monomer to moles of catalyst, with moles of catalyst being the denominator, so a larger ratio means less catalyst. In FIG. 1, three curves each represent different polymer compositions with different amounts of catalyst (M / C 20,000, 25,000, and 40,000, looking from left to right on the graph). Furthermore, as shown in FIG. 1, each composition has a different temperature at which decomposition begins. Thus, the thermal stability of the polymers of the present disclosure improves as the amount of catalyst decreases. For example, T3 has the least amount of catalyst, T2 has the next least, and T1 has the most catalyst in the polymer. Thermogravimetric analysis (TGA) was performed using a constant heating method from 20°C to 550°C at a rate of 20°C / min under nitrogen environment. All samples were dried at room temperature and under vacuum below 0.2 Torr for one week. Under these constant conditions, the effect of residual monomer content and catalyst concentration on thermal stability was isolated. Four lots of non-optimized high lactide copolymer were analyzed by TGA to determine the onset temperature of decomposition. Additionally, 35 lots of non-optimized high lactide copolymer were analyzed before and after extrusion to determine the intrinsic viscosity (IV) retention after extrusion. The results are shown in Table 1 below.

[0016] [Table 1]

[0017] In one embodiment, the lactide-based copolymer (more specific) reaction is carried out at two independent reaction temperature settings, with only the higher temperature resulting in low conversion (<92% conversion) and only the lower temperature resulting in excessive reaction times (>150 hours). The overall reaction with the combination of two independent reaction temperatures above and below the melt results in >92% conversion and <150 hours reaction time. The first reaction temperature is higher than the melt and the reaction is completed in the molten state. The second reaction temperature is carried out in the solid state and the polymer is crystallized. The reaction temperatures above and below the melt must differ by a minimum of 5°C, preferably 5-10°C, more preferably 10-20°C, and even more preferably >20°C from the solid state reaction temperature. The reaction temperature was measured at the bath temperature by a thermocouple. Under these conditions, the polymer is reacted in a batch process and there is no change in the reaction vessel. A change in vessel type gives potential contamination such as the introduction of moisture.

[0018] In another embodiment, the monomer to catalyst ratio of the prepolymer should be high enough that the total monomer to catalyst ratio after adding the second monomer charge having >50% lactide for the crystalline segment is higher than M / C of 25,000, more preferably >30,000, even more preferably >50,000, even more preferably >100,000. Lower M / C values ​​result in early reaction of the prepolymer with monomers that are prepared for end grafting in the subsequent reaction steps as described in the method of synthesis of the block copolymers of the present disclosure. Premature reaction prevents complete dissolution of the prepolymer in the liquid monomer, which is necessary for homogeneity before forming the endblock / end graft polymer chains on the prepolymer. The resulting change in solubility prevents complete dissolution of the prepolymer, and therefore contains a mixture of block copolymer and residual undissolved prepolymer that could not react with the monomer in the second charge. This result is confirmed by visual heterogeneity or by GPC analysis, as shown as a shoulder peak in Figure 9. Optionally, more catalyst may be added to the reaction vessel after complete dissolution and mixing of the prepolymer with the second charge, resulting in a decrease in M / C. In reactions such as these, where catalyst is fed in two or more steps during polymerization, it is necessary that the M / C is greater than 115K, 125K, 150K, 175K, 190K, 200K, 215K. The prepolymer may optionally be reacted with additional monomer to form flexible bond segments, followed by a third monomer or mixture of monomers to form endblocks. In both the second and third grafting reactions, it is desirable to have a consistent degree of polymerization for each polymer arm of the block copolymer, as well as the same degree of polymerization for the polymer chains of the bulk composition in the reactor. For GPC analysis, multimodal results are seen when there is essentially a blend of prepolymers that are unreacted or partially reacted with the block copolymer composed of prepolymers and terminal graft blocks. The prepolymers are inconsistent; some react and some do not react with the second charge of monomer. This results in a blended composition of different polymers, which may even be amorphous polymers distributed within the desired polymer.

[0019] Preferred catalysts for ring-opening polymerization include organotin compounds such as tin(II) 2-ethylhexanoate and dibutyltin oxide, but also other alternatives. In addition, suitable initiators for ring-opening polymerization include small molecules, oligomers, polymers, inorganic salts, and organic salts with hydroxyl groups. The initiator may be in the form of a small molecule with an average molar mass of less than 1000 g per mole, or less than 500 g per mole, or less than 300 g per mole, and the molar mass of the initiator is comparable to the average molar mass of a single monomer (the average molar mass of cyclic monomers such as lactones and carbonates typically has an average molar mass between 100 and 200 grams per mole). In some embodiments, the initiator comprises a single hydroxyl or amine group, or two or more hydroxyl or amine groups, or at least one amine group in combination with one or more hydroxyl groups, and the initiator may be in the form of a monofunctional hydroxyl- or amine-bearing species, or a polyol or polyamine with two or more reactive groups, or a hydroxyl-amino compound containing one or more hydroxyl groups and one or more amino groups. A combination of suitable initiators disclosed herein may be used in a single reaction to synthesize a mixture of different polymers that still have the same overall chemical composition of repeating units but have different architectures.

[0020] In some embodiments, the catalyst may serve as an initiator for the ring-opening polymerization of cyclic monomers, including, but not limited to, lactones, carbonates, and morpholinediones. Non-limiting examples of suitable monomers include lactides, such as L,L-lactide and D,L-lactide, glycolides, substituted glycolides, para-dioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, and delta-valerolactone. Additional monomers suitable for use in some embodiments include 5- and 7-membered cyclic esters, carbonates, and amides (e.g., cyclic amide-esters, also known as morpholinediones), which may be present in any combination. Substituted glycolides referred to in this disclosure may exhibit side groups other than protons at one or both methylene (-CH2-) carbons. Non-limiting examples of substituents include: saturated hydrocarbons having at least two carbons, which may be linear or branched and may be functionalized; some functional groups require protection prior to ring-opening polymerization and then deprotection once polymerization is complete; other functional groups do not interfere with the polymerization reaction and do not require protection / deprotection; some desirable functional groups may participate in the polymerization to give rise to secondary reactions such as branching of the main polymer chain axis, thereby allowing the formation of unique polymer structures such as hyperbranched polymers.

[0021] Additional substituents suitable for modifying glycolide may include aromatic groups having at least one carbon separating the aromatic group from a methylene carbon for the ring (to create a separation between the aromatic ring and the reactive site for the ring to prevent significant loss of reactivity). Other useful substituents may include unsaturated hydrocarbons having one or more carbon-carbon double bonds, where the unsaturation may be at the end of the hydrocarbon (i.e., vinyl end groups) or internal, and the unsaturated hydrocarbon may be aliphatic or aromatic. Additionally, halogens such as bromine and iodine may be used as suitable substituents - these may act as good leaving groups for secondary reactions during or after polymerization, and halogens may be able to impart radiopacity if the halogen atoms are present in high enough concentrations along the polymer chain.

[0022] Furthermore, the above-mentioned substituents may be present as a single substituent on the glycolide ring, or they may be present in various combinations. For example, they may be found overlapping and present on the same or opposite (para) carbons. Alternatively, two chemically different substituents may be present on the same ring, with the substituents present on the same or different carbons. Since the methylene carbon on glycolide exhibits sp3 hybridization, each of the two protons on the methylene carbon may be substituted as disclosed herein. Furthermore, the same or different substituents may be found on the same carbon. The chirality of the substituted glycolide is determined by the placement of the substituents along the ring. In another embodiment, the prepolymer must be heated to a minimum of 110° C., more preferably >115° C., more preferably >120° C., and even more preferably >130° C. in order to dissolve in the second charge.

[0023] In a further embodiment, the glycolide-based copolymer should have a monomer-to-catalyst ratio in the prepolymer that is sufficiently large that the M / C of the total monomer-to-catalyst ratio after adding the second monomer charge with >50% glycolide in the crystalline segment is greater than 90,000, more preferably >100,000, even more preferably >150,000, even more preferably >200,000. A high monomer-to-catalyst ratio in the prepolymer results in premature reaction of the prepolymer with the second charge, and therefore a change in solubility. The resulting change in solubility prevents complete dissolution of the prepolymer, and therefore a heterogeneous polymer with a mixture of block copolymer that could not react with the monomer in the second charge and remaining undissolved prepolymer. This result is confirmed by visual heterogeneity. Optionally, more catalyst is added to the reaction vessel after complete dissolution and mixing of the prepolymer with the second charge, resulting in a decrease in M / C. In reactions such as these in which the catalyst is fed in two or more steps during polymerization, it is necessary that M / C be greater than X to achieve complete solution and homogeneity. In another embodiment, the molecular weight of the prepolymer should be greater than 10 kDa, more preferably >15 kDa, and even more preferably >20 kDa. In another embodiment, the molecular weight of the prepolymer should be greater than 10 kDa, more preferably >15 kDa, even more preferably >20 kDa, even more preferably >30 kDa, even more preferably >50 kDa, even more preferably >60 kDa (including source). The molecular weight of the prepolymer is determined by GPC. The developmental lots synthesized for this disclosure used a lower catalyst concentration. The reaction temperature and time were modified to account for this change. Due to the lower catalyst concentration and new reaction conditions, the conversion of the optimized high lactide copolymer was expected to decrease and the residual monomer content to increase. The reaction conditions for each optimized lot are listed in Table 2 below.

[0024] [Table 2]

[0025] Table 3 below shows data comparing the area under the curve of the tested polymers and monomers by gel permeation chromatography (GPC). All optimized lots have high residual monomer content under the new reaction conditions. Lots 2d-4d have significantly higher residual monomer content. Lot 2d allows for improved conversion (lots 3d and 4d) by reacting at two independent temperature settings, one in the molten state and one in the solid state and with a temperature difference of 20° C. The results are shown in Table 3 by the reduction in residual monomer in lots 3d and 4d.

[0026] [Table 3]

[0027] The molecular weight and residual monomer content results after devolatilization for the control and optimized lots are shown in Table 4. The modified devolatilization procedure reduced the residual monomer content below the control value, with the average residual monomer content in the optimized lots being less than 1 wt%. Lots 1d and 4d, which contained high lactide block copolymer and were listed as SMC22, both had IVs outside the specification of >2.4 dL / g. Additionally, the PDI of each of the optimized lots with reduced catalyst concentrations decreased.

[0028] [Table 4]

[0029] The melt flow index (MFI) results for the optimized and control lots are shown in Table 5 below. MFI is commonly used to predict initial extrusion settings. Many properties of aliphatic polyesters affect MFI, including polymer molecular weight, residual monomer content, moisture content, temperature, pressure, and catalyst concentration. The method followed consisted of a constant temperature of 205°C and a constant mass of 3800 grams. Catalyst concentration and drying conditions remained constant in optimized lots 2d-4d. In these samples, the different MFI values ​​were a product of the variation in molecular weight and residual monomer concentration between the lots. Typically, melt viscosity is expected to be directly related to the molecular weight of the polymer (melt viscosity typically increases with increasing molecular weight). Furthermore, the residual monomer content will act as a plasticizer to reduce the melt viscosity. Comparing lot 4d with lots 3d and 2d, it is clear that the molecular weights of lots 3d and 2d are higher than lot 4d, but the melt viscosities of lots 3d and 2d are lower according to the MFI results. Thus, the lower monomer content in lot 4d appears to increase the melt viscosity by reducing the plasticizing effect of the monomer. In summary, melt viscosity typically increases with increasing molecular weight, but here it was seen that the residual monomer content, or the lack thereof, results in an increase in the melt viscosity of the low molecular weight polymer.

[0030] [Table 5]

[0031] The results of the onset temperature of decomposition are shown in Table 6 below. Each polymer was dried under constant conditions. Comparing Lot 1d to 4d, it is clear that Lot 1d has a lower onset temperature of decomposition (326.5°C) than Lot 4d (347.8°C). Both lots of polymer had similar residual monomer content, but Lot 4d had less catalyst, with a monomer to catalyst ratio of 40,000 compared to 25,000 for Lot 1d. In this example, the increased thermal stability of Lot 4d is shown by the increase in onset temperature of 21.3°C. Comparing Lot 4d to the control, Lot 4d had significantly less catalyst and residual monomer, and the onset temperature of Lot 4d was increased by 28.1°C compared to the control. The TGA graphs of the control, Lot 1d, and Lot 2d are shown in Figure 1. The effect of increasing thermal stability is supported by shifting the curve to the right, thereby increasing the onset temperature of decomposition.

[0032] [Table 6]

[0033] [Table 7]

[0034] Several embodiments are possible with the present disclosure. For example, Figures 6A and 6B show two embodiments of the present disclosure. Figure 6A shows a fully extended chain of a semi-crystalline multiaxial block copolymer, where both the end graft segments and the internal prepolymer derived segments are crystallizable. Figure 6A shows one embodiment of a multiaxial block copolymer 22 and a semi-crystalline end graft 20 of a semi-crystalline prepolymer 24. In another embodiment, Figure 6B shows another embodiment of the present disclosure. 6B shows an amorphous (non-crystallizable) multiaxial core 26 with three polymeric amorphous arms 28, each with a crystallizable end graft 30. 7A and 7B show two further alternative embodiments of the polymer constructs of the present disclosure. For 7A and 7B, the illustrated prepolymers can be amorphous or crystallizable. FIG. 7A shows a multiaxial block copolymer 32 without a flexible linker connecting prepolymer to end graft 36. Cross marks 38 represent the junction between prepolymer 34 and end graft 36, as well as the fully extended theoretical conformation of arm 40 of prepolymer 34. FIG. 7B shows a polymer construct 40 with a flexible linker 42 between block 44 derived from prepolymer 46 and end graft 48 with core 50 derived from prepolymer 46, which can be crystallizable or amorphous. End graft 48 can be amorphous or crystallizable. Flexible linker 42 has a minimum of 10 repeat units and can be derived from TMC in combination with other monomers as described herein.

[0035] Figure 8 is a chemical structure showing the repeat units forming a copolymer derived from glycolide and trimethylene carbonate (copolymer represented by elements 11, 12 and optionally 13 in Figure 11). An analysis of one embodiment of the polymer of Figure 8 is shown in Figure 10. X represents glycolide derived repeat units and Y is trimethylene carbonate derived repeat units. In one embodiment, the molar ratio of each of the chemical structures is X + Y = 1.0, where X is about 0.333 and Y is about 0.667. As shown in the figure, about 33 mole % and 67% (molar ratio) of the repeat units are derived from glycolide and trimethylene carbonate, respectively. The abbreviated polymer structure shown in FIG. 8 and shown on a larger scale in FIG. 11 may be synthesized in bulk or in solution, the reaction being carried out in the presence of an initiator and a catalyst, optionally in combination with an inert organic solvent for solution polymerization. In a preferred embodiment, the polymer is synthesized in bulk by ring-opening polymerization using a polyol initiator and tin(II) 2-ethylhexanoate as a catalyst. Preferably, the polyol has three or more reactive hydroxyl groups, so that the polymerization can result in a polymer with a star structure with three or more different polymer arms (the exact number of polymer arms or chains is equal to the number of reactive hydroxyl groups represented by the initiator). It is desirable for the polyol to exhibit symmetry, with the hydroxyl groups having identical or very similar reaction rates, which helps to ensure that similar chain lengths are obtained for each polymer arm (as shown in FIG. 11). Triethanolamine is an example of a suitable polyol for synthesizing the three-arm star copolymer shown in FIG. 11.

[0036] FIG. 11 is a diagram identifying the end blocks 14 of one of the three arms 11 of a multiaxial block copolymer 15, as well as the prepolymer segments 12 and flexible linkers 13. In one embodiment, the end blocks 14 are preferably formed entirely from glycolide-derived repeat units so that the end blocks can form highly crystalline physical crosslinks with the end blocks of other star block copolymers. In contrast, the prepolymer 16 can be formed from the prepolymer segments 12 and the flexible linkers 13. The prepolymer 16 is intended to be elastomeric and should exhibit minimal or preferably no crystallinity. The flexible linking segments 13 may covalently link the prepolymer segments 12 to the end blocks 14 for each arm 11. The flexible linkers 13 are preferably short linking segments of poly(trimethylene carbonate) that are amorphous throughout. While both arm 11 and prepolymer segment 12 are poly(glycolide-co-trimethylene carbonate), in one embodiment, arm 11 may contain a higher percentage of glycolide-derived repeat units than prepolymer segment 12. Due to the difference in reaction rates between glycolide and trimethylene carbonate (glycolide reacts faster), the chemical composition of the prepolymer should have decreasing glycolide content moving outward along the polymer chain until the terminal poly(glycolide) block is reached. Thus, once the synthesis is initiated, both glycolide and trimethylene carbonate react until all glycolide has reacted, at which point only trimethylene carbonate continues to react.

[0037] As the amount of glycolide decreases during the course of the reaction, segments represented by prepolymer segments 12 are synthesized, and if a significant amount of trimethylene carbonate remains, linking segments 13 may form without the need to add more trimethylene carbonate to the reaction vessel in the first reaction step. This situation is more likely to occur when the prepolymer is synthesized in the presence of less catalyst, as preferably taught by the present disclosure, and this mismatch in composition along the polymer chain is more likely to be seen when the reaction is carried out at lower temperatures, where the difference in the reaction rates of the monomers is more evident. However, if a higher reaction temperature is used during the prepolymer synthesis, a greater degree of randomization occurs and the glycolide is more evenly distributed. Additional trimethylene carbonate is then added to the reaction vessel and a second reaction step is required to synthesize the flexible linking segments, represented by linking segment 13. The final reaction step in either of these two different scenarios requires the addition of glycolide to the reaction vessel to graft it to the prepolymer and form endblocks on all three polymer chains. For this polymerization to be successful, the use of a minimum amount of catalyst (preferably a total monomer to catalyst molar ratio of greater than 150,000 is required, but it is more preferable to use a higher monomer to catalyst ratio, e.g., 200,000) is necessary, especially when a high proportion of prepolymer is sought in the final polymer, as in the case of FIG. 11, where the prepolymer may comprise 30-45% by weight (preferably 35%) of the total polymer, and when the final reaction step requires the complete dissolution of the prepolymer in the molten glycolide followed by an increase in temperature to synthesize the endblocks. In the two-step reaction, elements 11, 12, and 13 are considered to be the prepolymer. In the three-step reaction, elements 11 and 12 represent two distinct regions of different composition in the prepolymer based on the difference in reaction rate. In both cases, in the two-step and three-step reactions, element 13 is considered to be the flexible linker.

[0038] 12 shows an alternative embodiment of a multiaxial block copolymer 59 containing multiple segments. Segmented prepolymer 61 is composed of random regions 60 and transitional regions 62. 60 and 62 represent two distinct regions in the prepolymer, in one embodiment containing a majority of glycolide units (60), and transitional region 62 where fewer glycolide repeat units form primarily from slower reaction rates. Flexible linkers 64 may be formed in a separate reaction step after synthesis of segmented prepolymer 61. End grafts 66 may optionally be high glycolide or high lactide end blocks. FIG. 13 illustrates a four-arm multiaxial copolymer 80 including arms 82, 84, 86, and 88. All four arms 82, 84, 86, and 88 include a microstructure 90. In one embodiment, arm 82 is a single arm of a four-arm multiaxial copolymer. Arm 82 may be a vertically oriented crystalline lamella composed of many individual arms of the same composition 92. Arms 82 and 86 may be crystalline and 84 and 88 may be amorphous. 82 and 86 and 84 and 88 may have variable "widths" such that there is variable spacing between the arms. The chemical composition of the opposing arms in FIG. 13 is substantially the same as in FIG. 13. FIG. 13 illustrates a four-arm multiaxial star polymer composed of two types of polymer arms--amorphous and semi-crystalline. The four arms are oriented around a central vertical axis 94 that runs through the center of the copolymer 80.

[0039] FIG. 14 is an excerpt from FIG. 13 showing the folding of polymer chains of an exemplary arm 96 resulting in a chain-folded crystal. Thus, the semi-crystalline arms 82, 84, 86 and 88 of FIG. 13 reptile parallel or nearly parallel to the Z axis and outward from the Z axis as a crystalline lamellar form as shown in FIG. 14. Additional 4-arm star polymers "stack" vertically and contribute to the crystal growth. The vertical incorporation of polymer chains results in vertical stacking and growth of crystalline domains along the Z axis as shown in FIG. 13. Additionally, amorphous domains form from combinations of chains that extend outward from the Z axis and connect to the crystallizing polymer chains, exit the crystalline lamella along the chains and intertwine with the amorphous phase, often re-entering the crystalline microstructure and forming "loops" on the lamellar faces that are joined together to form organized structures with two similar arms each positioned opposite each other in the same plane. 15 is a diagram illustrating an asymmetric multiaxial copolymer 100. In the illustrated embodiment, two arms 102 and 104 are chemically similar in composition, while the third arm 106 is different in chemical composition. Arm 102 is composed of an inner amorphous block 108 formed as an arm of a prepolymer 112, and an outer semi-crystalline block 110 covalently bonded thereto. Arm 106, which may be formed in a different reaction step than arms 102 and 104, may be formed in a first reaction step, followed by a second reaction step to form arms 102 and 104. Alternatively, arm 106 may be formed as part of an initial reaction step, with arms 102, 104 and 106 being chemically similar in composition. For example, a two-step reaction may be used to form a three-arm amorphous prepolymer, in which one terminal hydroxyl group may be protected on the surface, or optionally fixed to the surface, prior to the second reaction step which requires a ring-opening polymerization to end-graft a terminal crystallizable block onto the two unprotected prepolymer arms.

[0040] FIG. 16 illustrates a single microstructure 120 showing individual polymers 122 that may be considered hyperbranched. The core 124 is formed by unoriented amorphous irregular polymer chains 126 that are initiated at a central location 128, essentially or substantially at the center of the microstructure 120, where the unoriented polymer chains 126 transition to an outer semi-crystalline block 130. The block 130 may crystallize as shown in FIG. 14 by forming a crystalline structure in which the chains are folded. The microstructure 120 of FIG. 16 may be used as a drug delivery system via the large void volume 125 of the chains 126 to allow a bioactive agent, not shown, to be dispersed within the structure of the chains 126. The size and concentration of the bioactive agent that may be loaded into the core 124 depends on the number of polymer chains 126, which directly affects the total available void volume that may be occupied by the bioactive agent. The outer shell 132, by chain folding of the semi-crystalline blocks 130, forms a tough protective shell that acts as a protective layer for the voids 125 and bioactive agent dispersed therein. The bioactive agent may be substantially contained within the voids 125 until the shell 132 degrades sufficiently to allow sufficient porosity for diffusion of the bioactive agent through the shell 132. The shell 132 may be designed to allow initial bioactive release followed by increasing bioactive release as the shell further degrades. It is preferred to avoid defects in the shell to provide protection for the voids 125. In a preferred embodiment, the end blocks 130 may be synthesized using a single monomer to allow for a uniform crystalline structure. Multiple microstructures 120 may be used together and overlap each other in the shell 132 to form crystalline domains between adjacent microstructures 120. The microstructures 120 may be formed into a film or used as individual spheres to allow for the dispersion of the bioactive agent in a desired form over a desired time span.

[0041] In other preferred embodiments, it is desirable to form different polymer architectures such as linear (unidirectional and bidirectional), multiaxial, star, branched, graft, comb, brush, circular, and combinations thereof. However, the same concept of utilizing minimal catalyst is still necessary since it is necessary to improve the thermal stability of the copolyesters (in addition to promoting intimate mixing of the prepolymer with the monomer as a second / final reaction step) so that they can be processed above the melting point of the polymer without causing excessive or significant degradation. Absorbable fibers can be produced from the polymers of the present disclosure via melt extrusion and electrospinning techniques as known to those skilled in the art. These fibers can be formed into solid constructs such as barriers, webs, meshes, or fabrics (woven or nonwoven) via methods known to those skilled in the art. Alternatively, partially absorbable constructs can be formed by combining absorbable polymers and fibers derived therefrom with nonabsorbable fibers derived from materials such as polyurethane, polypropylene, polyethylene, polyetheretherketone (PEEK), and polyethylene terephthalate.

[0042] In one embodiment, the mesh can be constructed by warp knitting and weft knitting. The particular knitting pattern can be chosen depending on the mechanical strength requirements of a particular medical application. Different techniques for forming fibrous constructs can also be combined in unique ways to create hybrid constructs. For example, a warp knitted mesh can be electrospun to obtain an electrospun surface or layer. Indeed, the polymers of the present disclosure are suitable as medical grade polymers for incorporation into various medical devices, such as absorbable or partially absorbable meshes, pouches, containers, barriers, support structures, etc., that can be formed from the polymers of the present disclosure. For example, FIG. 2 illustrates an embodiment of the present disclosure in which a warp knitted 3-bar construction may be used. The 3-bar pattern may be advantageous for improved dimensional and mechanical properties, especially improved weft direction stability. Additionally, the 3-bar pattern typically produces a "heavier" fabric. In one embodiment, fabrics made using the warp knitted 3-bar construction may be used for sealing applications. In one embodiment, a 3-bar configuration of bar 1: 1-0-0 / 0-1-1, bar 2: 2-3-2 / 1-0-1, bar 3: 1-0-1 / 1-2-1 may be used. Meanwhile, Figure 3 shows an embodiment of the present disclosure in which a warp knit two-bar construction may be used. In one embodiment, a tricot fabric may be produced. Tricot is a simple construction that provides a lightweight fabric with a short underlap. In one embodiment, a two-bar configuration may be used, including bar 1:1-2 / 1-0 and bar 2:1-0 / 1-2.

[0043] FIG. 4 illustrates another warp knit two-bar structure known as "sharkskin." Sharkskin is a simple two-bar structure, but with a longer swing distance resulting in increased stability and increased areal density. Additionally, the sharkskin pattern exhibits reduced shrinkability, thus providing a more rigid and stable structure. Additionally, the surface texture of the sharkskin structure is "rough" and can be used in medical applications where it is desired to create adhesion. In one embodiment, a two-bar structure may be used, where bar 1: 1-2-2 / 1-0-0 and bar 2: 1-0-1 / 3-4-3. FIG. 5 shows a half tricot pattern that may be used in the present disclosure. The half tricot pattern results in a low areal density construction, thereby providing a very light construction. Although not as strong as tricot, it is easier to manufacture, requires less material, and is a simple construction. In one embodiment, a construction with bar designations of 1-2 / 1-0 may be used. This is an example of a half tricot pattern, where the "1-2" means that the guide bars overlap when moving from right to left for one needle from position 1 to position 2. The "1-0" means that the needles are fed from left to right.

[0044] 6A and 6B show the multiaxial structure of absorbable block copolymers comprising a prepolymer, which may be amorphous or crystallizable, and a structure further comprising a flexible linking segment between the polymeric axis derived from the prepolymer and the terminal grafted end block. Suitable flexible linking segments may be derived from trimethylene carbonate and epsilon-caprolactone, optionally in combination. If epsilon-caprolactone is selected for the flexible linking segment, it is necessary to ensure that the segment remains amorphous and that the chain length does not exceed the crystallization threshold of caprolactone. In one preferred embodiment, the prepolymer is derived from glycolide and trimethylene carbonate and is amorphous, the flexible linking segment is derived from trimethylene carbonate, and the terminal grafted block is derived from glycolide. Optionally, the flexible linker is formed as a result of reaction parameters that allow excess trimethylene carbonate to remain during the first polymerization reaction to form the prepolymer, so that the remaining trimethylene carbonate can react to form the flexible linker after the prepolymer is formed. The second method of forming the linker is to react the prepolymer at high temperature to ensure randomization of the prepolymer and non-segmentation of the trimethylene carbonate at the end of the prepolymer, followed by adding more trimethylene carbonate to the reaction vessel to form the linking segment. Glycolide is added to the reaction vessel to react the trimethylene carbonate to completion before forming the terminal graft block. The properties of the polymers produced according to this procedure are shown in Table 8.

[0045] [Table 8]

[0046] In some embodiments, the fully or partially absorbable barriers, webs, meshes or fabrics of the present disclosure may further comprise a method of delivering one or more bioactive or therapeutic agents as well as therapeutic agents, comprising applying a mesh or web to a treatment site, wherein the mesh or web comprises at least one type of polymeric fiber and one or more bioactive and / or therapeutic agents. In some embodiments, the mesh or web may contain an absorbent polymer surface coating for controlled drug delivery, with one or more bioactive and / or therapeutic agents dispersed throughout the coating. Alternatively, the mesh or web may contain fibers impregnated with one or more bioactive and / or therapeutic agents (see, e.g., U.S. Patent No. 8,128,954, incorporated in its entirety).

[0047] In some embodiments, the polymeric surface coating may have multiple coatings or layers of absorbent aliphatic polyester, and the coating may be applied to the mesh surface. The different coating layers may contain the same or different bioactive and / or therapeutic agents, with the agents present in the same or different concentrations in each layer. In some embodiments, the coating is comprised of multiple layers, and there is a concentration gradient of the bioactive and / or therapeutic agents from the innermost layer to the outermost layer, so that the concentration is highest in the innermost coating layer and lowest in the outermost coating layer. The bioactive and / or therapeutic agents may be dispersed within each of the coating layers, or they may be dispersed in only a portion of the layer, or they may be dispersed in alternating coating layers, so that alternating layers are devoid of bioactive and / or therapeutic agents. Additionally, the outermost layer may be completely devoid of bioactive and / or therapeutic agents to reduce the possibility of a burst release effect. When a gradient concentration design is utilized to distribute one or more bioactive and / or therapeutic agents throughout the coating layers, it is preferable to have a concentration gradient that decreases from the innermost layer closest to the mesh surface to the outermost layer, which is the outermost of all layers. The concentration gradient is intended to reduce, if not eliminate, the initial burst release of bioactive and / or therapeutic agent from the surface of the coating shortly after implantation of the mesh.

[0048] In some embodiments, the coating polymer is a high molecular weight caprolactone-based copolymer, where caprolactone-derived repeat units constitute more than 50% of the repeat units in the total composition, and the remaining repeat units can be derived from a monomer selected from L-lactide, glycolide, trimethylene carbonate, and para-dioxanone. When multiple coating layers constitute the surface coating on the mesh or web, each layer can be formed from the same or different caprolactone-based copolymer. Different copolymers are used when it is desired to adjust the hydrophobic properties of different coating layers. Copolymers with higher caprolactone content are more hydrophobic than copolymers with lower caprolactone content. In some embodiments, it is desirable to have a composition gradient in different coating layers. For example, the innermost layer can be formed from a copolymer that is 90 mole % caprolactone, followed by 80%, 70% and 60% in the adjacent outer layers, with the caprolactone content (and hydrophobic properties) decreasing from 90% to 60% from the innermost layer to the outermost layer. The coating polymer of the present invention is a copolymer of caprolactone and trimethylene carbonate.

[0049] In further embodiments, the prepolymer may comprise a semi-crystalline aliphatic polyester copolymer having a heat of fusion of <75 J / g, preferably <70 J / g, more preferably <65 J / g, even more preferably <55 J / g, even more preferably <45 J / g, even more preferably <35 J / g as measured by DSC. The prepolymer may comprise cyclic monomers such as glycolide, lactide, para-dioxanone, trimethylene carbonate, morpholinedione, and mixtures thereof. The melting point of the prepolymer may be <170°C, more preferably <150°C, even more preferably <120°C, even more preferably <100°C as measured by DSC. The resulting prepolymer may be reacted with a flexible linker prior to crystalline end grafting. The flexible linker comprises a minimum of 10 repeating units, more preferably >20, even more preferably >30 repeating units, even more preferably >40. The flexible linker may include amorphous segments with compositions including cyclic monomers such as glycolide, lactide, para-dioxanone, ε-caprolactone, trimethylene carbonate, morpholinedione, and mixtures thereof. The crystalline end graft may be a high lactide copolymer containing a small amount of at least one additional monomer. By "high", it is meant that the polymer may contain at least 50 mole % lactide derived repeat units, at least 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or more lactide derived repeat units. Ranges of lactide molar content are also contemplated within the scope of the present disclosure, including ranges of 50-60%, 60-70%, 70-80%, 80-90%, and 90-100%. Additionally, the crystalline end grafts may contain at least 50 mole % glycolide derived repeat units, at least 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or more glycolide derived repeat units. (See FIG. 12.) Ranges of glycolide molar content are also contemplated within the scope of the present disclosure, including ranges of 50-60%, 60-70%, 70-80%, 80-90%, and 90-100%. (See FIG. 12.) The overall polymer may contain initiators that are linear or polyaxial.

[0050] In further embodiments, a second polymer may be combined or blended with the improved block copolymer of the present disclosure. The second polymer may be a reinforcing additive that provides higher strength to compositions containing the block copolymer. This is particularly suitable when the amount of prepolymer present in the block copolymer exceeds 25% by weight of the total polymer, and even more so when the prepolymer approaches 50%. The additional polymer may actually crystallize the block copolymer in the presence of the additive, which would otherwise not be able to crystallize to the extent necessary to provide the desired mechanical strength. This results in a higher degree of crystallinity or percent crystallinity of the blended composition. Furthermore, the reinforcing polymer may have a chain length of about twice the chain length of a single end block of the block copolymer. The additional reinforcing polymer may not have a shorter chain length since it does not reinforce the block copolymer by forming physical entanglements between two or more end blocks of the block copolymer disclosed herein, which may be linear or multiaxial. The reinforcing polymer may have the same theoretical chemical composition and therefore may be derived from the same monomers as the repeating units that form the end blocks of the block copolymer. The polymerization of the endblocks may include residual monomers from the reaction forming either the prepolymer or the flexible linking segment.

[0051] Applying the surface coating to the mesh construct can be accomplished by dip-coating or spray-coating techniques using a liquid solution of a polymer mixed with one or more therapeutic agents at a specific concentration. Alternatively, the liquid solution may contain a polymer without a therapeutic agent. Mixing and dissolving can be accomplished by combining a caprolactone-based coating polymer with a common organic solvent and a specific amount of therapeutic agent. This results in a solution with a specific concentration of therapeutic agent that can be applied to the mesh surface by dip-coating or spray-coating. Different solutions can be applied sequentially to the mesh surface to form multiple coating layers. Each solution can contain different concentrations of one or more therapeutic agents, so that a concentration gradient can be created throughout the surface coating, and / or each solution can contain a polymer with different hydrophobic properties. In alternative embodiments, the biocompatible polymer composition containing the therapeutic agent can be prepared by cold processing or hot processing depending on the heat resistance of the therapeutic agent. For therapeutic agents that are susceptible to inactivation by heat, cold processing is preferred. In summary, the polymeric components of the mesh or web, the major component, minor component, or both, can be completely melted in the absence of the therapeutic agent. The molten composition is cooled below room temperature to retard crystallization of the polymer in the composition. In certain embodiments, cooling is performed at a rate of about 10° C. per minute. The therapeutic agent is then added to the molten composition below room temperature and thoroughly mixed with the composition to produce a homogeneous blend. Depending on the type of material, a solution-based mixing procedure may be used.

[0052] In alternative embodiments, the barriers, meshes or webs of the present disclosure may have bioactive and / or therapeutic agents applied to one or more specific portions of the mesh or web, as opposed to the entire construct. Within certain embodiments, the mesh or web may be dip- or spray-coated with one or more bioactive agents or with a composition that releases one or more bioactive agents over a desired time frame. In yet other embodiments, the fibers themselves may be configured to release a bioactive agent (see, for example, U.S. Patent No. 8,128,954, incorporated in its entirety). Therapeutic agents may include fibrosis-inducing agents, antifungal agents, antibacterial agents, anti-inflammatory agents, anti-adhesion agents, bone formation promoters, mineralization promoters, antimicrobial agents, antibiotics, immunosuppressants, immunostimulants, antiseptics, anesthetics, antioxidants, cell / tissue growth promoters, lipopolysaccharide complexing agents, anti-scarring agents, anti-neoplastic agents, anti-cancer agents, and agents that support ECM integration.

[0053] Examples of fibrosis inducers include talc powder, metallic beryllium and its oxide, copper, silk, silica, crystalline silicates, talc, quartz powder, and ethanol; extracellular matrix components selected from fibronectin, collagen, fibrin, or fibrinogen; polymers selected from the group consisting of polylysine, poly(ethylene-co-vinyl acetate), chitosan, N-carboxybutyl chitosan, and RGD protein; vinyl chloride or polymers of vinyl chloride; cyanoacrylates and cross-linked poly(ethylene glycol)-methyl inflammatory cytokines (e.g., TGF-beta, PDGF, VEGF, bFGF, TNF-alpha, NGF, GM-CSF, IGF-a, IL-1, IL-1-beta, IL-8, IL-6, and growth hormone); connective tissue growth factor (CTGF); bone morphogenetic proteins (BMPs) (e.g., BMP-2, BMP-3, BMP-4, BMP-5, BMP-6, or BMP-7); leptin, and bleomycin or analogs or derivatives thereof. Optionally, the device may further comprise a growth agent to stimulate cell proliferation. Examples of proliferation agents may include dexamethasone, isotretinoin (13-cis retinoic acid), 17-e-estradiol, estradiol, 1-a-25 dihydroxyvitamin D3, diethylstilbesterol, cyclosporine A, L-NAME, all-trans retinoic acid (ATRA), and analogs and derivatives thereof (see U.S. Patent Application Publication No. 2006 / 0240063, which is incorporated by reference in its entirety).

[0054] Examples of antifungal agents include, but are not limited to, polyene antifungals, azole antifungals, and echinocandins. Examples of antibacterial agents and antibiotics include, but are not limited to, erythromycin, penicillin, cephalosporins, doxycycline, gentamicin, vancomycin, tobramycin, clindamycin, and mitomycin. Examples of anti-inflammatory agents include, but are not limited to, nonsteroidal anti-inflammatory agents such as ketorolac, naproxen, diclofenac sodium, and flurbiprofen. Examples of anti-adhesion agents include, but are not limited to, talc powder, metallic beryllium and its oxides, copper, silk, silica, crystalline silicates, talc, quartz powder, and ethanol. Examples of bone formation or mineralization promoters include, but are not limited to, hydroxyapatite, tricalcium phosphate, calcium chloride, calcium carbonate, calcium sulfate, bioactive glass, bone morphogenetic proteins (BMPs), such as BMP-2, BMP-3, BMP-4, BMP-5, BMP-6, and BMP-7. Examples of immunosuppressants include, but are not limited to, glucocorticoids, alkylating agents, antimetabolites, and agents that act on immunophilins such as cyclosporine and tacrolimus.

[0055] Examples of immune stimulatory agents include, but are not limited to, interleukins, interferons, cytokines, Toll-like receptor (TLR) agonists, cytokine receptor agonists, CD40 agonists, Fc receptor agonists, CpG-containing immune stimulatory nucleic acids, complement receptor agonists, or adjuvants. Examples of antiseptics include, but are not limited to, chlorhexidine and tibezonium iodide. Examples of antioxidants include, but are not limited to, antioxidant vitamins, carotenoids, and flavonoids. Examples of anesthetic agents include, but are not limited to, lidocaine, mepivacaine, pyrrocaine, bupivacaine, prilocaine, and etidocaine. Examples of cell growth promoting factors include, but are not limited to, epidermal growth factor, human platelet-derived TGF-B, endothelial cell growth factor, thymocyte activating factor, platelet-derived growth factor, fibroblast growth factor, fibronectin or laminin. Examples of lipopolysaccharide complexing agents include, but are not limited to, polymyxins. Examples of peroxides include, but are not limited to, benzoyl peroxide and hydrogen peroxide.

[0056] Examples of anti-neoplastic / anti-cancer agents include, but are not limited to, paclitaxel, carboplatin, miconazole, leflunamide, and ciprofloxacin. Examples of anti-scarring agents include, but are not limited to, cell cycle inhibitors such as taxanes, immunomodulators such as serolimus or viola (see, e.g., paras. 64-363; see also our co-presidential U.S. Patent Application Publication No. 2005 / 0149158, which is incorporated herein by reference in its entirety). An example of an agent that supports ECM integration includes, but is not limited to, gentamicin. It is recognized that in certain therapeutic modalities, combinations of substances / agents in the same polymer composition may be effective to obtain optimal efficacy. Thus, for example, an antimicrobial agent and an anti-inflammatory agent may be combined in a single copolymer to provide the benefits of both. The disclosure herein may be used in connection with injection molded articles, films, non-porous films, drug delivery vehicles, particulate micro / nano drug delivery vehicles, meshes, nonwoven articles, knits, woven fabrics, surgical meshes, bioabsorbable stents for body lumens, 3-D printed articles, drug coatings, temporary implants and components thereof, and in situ forming medical articles.

[0057] Unless otherwise stated, terms and phrases used herein, and variations thereof, unless expressly stated otherwise, should be construed as open ended rather than limiting. Similarly, a group of items joined with the conjunction "and" should not be read as requiring each and every item to be present in the group, but should be read as "and / or" unless otherwise stated. Similarly, a group of items joined with the conjunction "or" should not be read as requiring mutual exclusivity between the group, but should be read as "and / or" unless otherwise stated. Additionally, although items, elements, or components of the disclosure may be described or claimed in the singular, the plural is contemplated within its scope unless limitation to the singular is expressly stated. The presence of broad phrases such as "one or more," "at least," "but not limited to," or other similar phrases shall not be read to imply that a narrower example is intended or required where such broad phrase may not be present. While the subject matter has been described in detail with respect to certain exemplary embodiments and methods thereof, those skilled in the art will appreciate that, upon achieving the above understanding, modifications, variations, and equivalents of such embodiments may be readily effected. Accordingly, the scope of the present disclosure is by way of example and not limitation, and the disclosure of the subject matter does not exclude including such modifications, variations, and / or additions to the subject matter as would be readily apparent to one of ordinary skill in the art using the teachings disclosed herein.

Claims

1. A thermally stable and absorbent aliphatic polyester copolymer having a delayed thermal decomposition onset temperature compared to a corresponding aliphatic polyester copolymer prepared with a molar ratio (M / C) of 35,000 of the total amount (M) of a first cyclic monomer and a second cyclic monomer to the total amount (C) of a ring-opening polymerization catalyst, the polyester copolymer having (1) an amorphous prepolymer forming at least three axes, and (2) a crystalline end graft extending from each of the amorphous prepolymers, (a) the amorphous prepolymer is selected from a homopolymer, copolymer, or terpolymer comprising a first cyclic monomer selected from L,L-lactide, D,L-lactide, glycolide, a substituted glycolide, para-dioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, and delta-valerolactone, or a combination thereof, and is prepared in the presence of an initiator having a plurality of alcohol groups and in the presence of the ring-opening polymerization catalyst; (b) a second cyclic monomer selected from L,L-lactide, D,L-lactide, glycolide, a substituted glycolide, para-dioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, and delta-valerolactone, or combinations thereof, is grafted to the amorphous prepolymer in the presence of the amorphous prepolymer and in the presence of the ring-opening polymerization catalyst; A thermally stable and absorbent aliphatic polyester copolymer, characterized in that the molar ratio of the total amount of said first cyclic monomer and said second cyclic monomer to the total amount of said ring-opening polymerization catalyst is greater than either 50,000 or 100,000.

2. A thermally stable and absorbent aliphatic polyester copolymer having a delayed thermal decomposition onset temperature compared to a corresponding aliphatic polyester copolymer prepared with a molar ratio (M / C) of 35,000 of the total amount (M) of a first cyclic monomer and a second cyclic monomer to the total amount (C) of a ring-opening polymerization catalyst, the polyester copolymer having (1) crystallizable prepolymers forming at least three axes, and (2) crystallizable terminal grafts extending from each of the crystallizable prepolymers, (a) the crystalline prepolymer is selected from a homopolymer, copolymer, or terpolymer comprising a first cyclic monomer selected from L,L-lactide, D,L-lactide, glycolide, a substituted glycolide, para-dioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, and delta-valerolactone, or a combination thereof, and is prepared in the presence of an initiator having a plurality of alcohol groups and in the presence of the ring-opening polymerization catalyst; (b) a second cyclic monomer selected from L,L-lactide, D,L-lactide, glycolide, a substituted glycolide, para-dioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, and delta-valerolactone, or combinations thereof, is grafted to the crystalline prepolymer in the presence of the crystalline prepolymer and in the presence of the ring-opening polymerization catalyst; A thermally stable and absorbent aliphatic polyester copolymer, characterized in that the molar ratio of the total amount of said first cyclic monomer and said second cyclic monomer to the total amount of said ring-opening polymerization catalyst is greater than either 50,000 or 100,000.

3. A thermally stable and absorbent aliphatic polyester copolymer having a delayed thermal decomposition onset temperature compared to a corresponding aliphatic polyester copolymer prepared with a molar ratio (M / C) of 35,000 of the total amount (M) of a first cyclic monomer and a second cyclic monomer to the total amount (C) of a ring-opening polymerization catalyst, the copolymer comprising: (1) semi-crystalline aliphatic polyester prepolymers forming at least three axes; (2) crystalline end grafts from each of the semi-crystalline aliphatic polyester prepolymers; and (3) optionally a flexible linker between the semi-crystalline aliphatic polyester prepolymers and the crystalline end grafts. (a) the semi-crystalline aliphatic polyester prepolymer is selected from a homopolymer, copolymer, or terpolymer comprising a first cyclic monomer selected from glycolide, lactide, para-dioxanone, trimethylene carbonate, and morpholinedione, or a combination thereof, and is prepared in the presence of an initiator having a plurality of alcohol groups and in the presence of the ring-opening polymerization catalyst; (b) a second cyclic monomer selected from L,L-lactide, D,L-lactide, glycolide, a substituted glycolide, para-dioxanone, 1,5-dioxepan-2-one, trimethylene carbonate, epsilon-caprolactone, alpha-angelica lactone, gamma-valerolactone, and delta-valerolactone, or combinations thereof, is grafted to the semi-crystalline aliphatic polyester prepolymer in the presence of the semi-crystalline aliphatic polyester prepolymer and in the presence of the ring-opening polymerization catalyst; A thermally stable and absorbent aliphatic polyester copolymer, characterized in that the molar ratio of the total amount of said first cyclic monomer and said second cyclic monomer to the total amount of said ring-opening polymerization catalyst is greater than either 50,000 or 100,000.

4. 4. The thermally stable and absorbent aliphatic polyester copolymer of claim 3, wherein said crystalline end grafts comprise 80-90 mole % lactide.

5. 4. The thermally stable and absorbent aliphatic polyester copolymer of claim 3, wherein said crystallizable end grafts comprise at least 50 mole percent glycolide as the second cyclic monomer.

6. 4. The thermally stable and absorbent aliphatic polyester copolymer of claim 3, wherein the flexible linker comprises a third cyclic monomer selected from glycolide, lactide, para-dioxanone, epsilon-caprolactone, trimethylene carbonate, and morpholinedione, or a combination thereof.

7. 4. The thermally stable and absorbent aliphatic polyester copolymer of claim 1, wherein the initiator is selected from 1-decanol, 1,3-propanediol, trimethylolpropane, triethanolamine, 1,3,4-trihydroxy-2-butanone, and glycerol, or a combination thereof.

8. The ring-opening polymerization catalyst is stannous octoate, Sn(Oct) 2 , Sn(OTf) 2 , dibutyltin(II)-2-ethylhexanoate (Bu 2 Sn(Oct) 2 4. The heat-stable and absorbent aliphatic polyester copolymer according to claim 1, wherein the copolymer is selected from the group consisting of 4-(dimethylamino)pyridine (DMAP), 4-(dimethylamino)pyridine (DMAP), and 4-(dimethylamino)pyridine (DMAP).

9. The thermally stable and absorbent aliphatic polyester copolymer of any one of claims 1 to 3, wherein the crystallizable end grafts comprise at least 50 mol % glycolide as the second cyclic monomer.

10. The thermally stable and absorbent aliphatic polyester copolymer of any one of claims 1 to 3, wherein the crystallizable end grafts comprise at least 50 mol % of lactide as the second cyclic monomer.

11. 10. The thermally stable and absorbent aliphatic polyester copolymer of claim 1, wherein the amorphous prepolymer comprises trimethylene carbonate (TMC) as a first cyclic monomer.

12. 3. The thermally stable and absorbent aliphatic polyester copolymer of claim 2, wherein the crystalline prepolymer comprises trimethylene carbonate as a first cyclic monomer.

13. 2. The thermally stable and absorbent aliphatic polyester copolymer of claim 1, wherein the amorphous prepolymer comprises trimethylene carbonate and epsilon-caprolactone as first cyclic monomers.

14. 10. The thermally stable and absorbent aliphatic polyester copolymer of claim 1, wherein said crystalline end grafts contain at least 90 mole percent glycolide.

15. 3. The thermally stable and absorbent aliphatic polyester copolymer of claim 2, wherein said crystalline end grafts contain at least 90 mole percent glycolide.

16. 2. The thermally stable and absorbing aliphatic polyester copolymer of claim 1, wherein said ring-opening polymerization catalyst is stannous octoate.

17. 10. The thermally stable and absorbent aliphatic polyester copolymer of claim 1, wherein the amorphous prepolymer has a molecular weight greater than 10 kDa.

18. 10. The thermally stable and absorbent aliphatic polyester copolymer of claim 1, wherein said amorphous prepolymer has a molecular weight greater than 20 kDa.

19. A fibre comprising the heat-stable and absorbent aliphatic polyester copolymer according to any one of claims 1 to 18.

20. 20. An absorbent barrier, web, mesh or fabric comprising the fibers of claim 19.

21. 20. A warp knit mesh comprising the fibers of claim 19.

22. An absorbent polymeric surface coating for controlled drug delivery, comprising an aliphatic polyester copolymer according to any one of claims 1 to 18.